Dispersion of subsurface lagrangian drifters in the northeastern Gulf of Mexico - Hancock, Cathrine; Speer, Kevin; de Souza, Joao Marcos Azevedo Correia; Morey, Steven L. (Frontiers in Marine Science, 2022)
The dispersion of subsurface Lagrangian floats by eddies was observed directly in DeSoto Canyon, located in the northeastern Gulf of Mexico. Key elements of dispersion include the capture and release of floats by variations in eddy structure and intensity. Two separate eddy events were revealed through 60-day trajectories from five subsurface drifters deployed at 400 m depth in DeSoto Canyon. A changing background flow in DeSoto Canyon allowed for the contraction and expansion of the eddy’s “trap zone,” resulting in the capture and release of several drifters deployed in the area. To investigate the variability of dispersion due to this capture-and-release effect, virtual particle tracks from a 5-year numerical model simulation of the Gulf of Mexico were used. Large interannual variability was observed in eddy activity over the 5-year simulation. When coupled with a variable background flow, this greatly affected Lagrangian particle transport within the entire eastern Gulf of Mexico. During years of increased eddy activity, more virtual particles were “captured” from the along-slope flow and “released” offshore, increasing dispersion and residence time within the eastern Gulf of Mexico. The opposite was observed during minimal eddy activity, where more virtual particles remained within the along-slope flow and thus were funneled toward two main exit points out of the eastern Gulf of Mexico. Regions such as DeSoto Canyon with strong topographic constraints, a highly variable background flow, and considerable eddy activity are likely to spread tracers such as nutrients and contaminants over a substantial area due to this capture-and-release effect.